2019
DOI: 10.1111/jfb.13996
|View full text |Cite
|
Sign up to set email alerts
|

Manual fish length measurement accuracy for adult river fish using an acoustic camera (DIDSON)

Abstract: Total lengths (LT) of 50 free‐swimming fish in a tank, silver carp Hypophthalmichthys molitrix and rainbow trout Oncorhynchus mykiss, were measured using a DIDSON (Dual‐frequency IDentification SONar) camera. Using Sound Metrics software, multiple measurements of each fish (LT, side aspect angle and distance from the camera) at different times were analysed by two experienced operators while a subset of data was analysed by two inexperienced operators. The main result showed high variability in intra‐fish LT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Many previous studies have reported that there is no range dependency in the accuracy of the length estimates using high-frequency mode and a shorter range (Burwen et al, 2010;Daroux et al, 2019;Gurney et al, 2014;Hightower et al, 2013). Burwen et al (2007) found no range-dependent bias on free-swimming fish but found it on tethered fish, and had a lower measurement accuracy on tethered fish.…”
Section: Data Quality Assessment and Influence Of Range On The Measmentioning
confidence: 97%
See 2 more Smart Citations
“…Many previous studies have reported that there is no range dependency in the accuracy of the length estimates using high-frequency mode and a shorter range (Burwen et al, 2010;Daroux et al, 2019;Gurney et al, 2014;Hightower et al, 2013). Burwen et al (2007) found no range-dependent bias on free-swimming fish but found it on tethered fish, and had a lower measurement accuracy on tethered fish.…”
Section: Data Quality Assessment and Influence Of Range On The Measmentioning
confidence: 97%
“…In the last 5-10 years, the use of automatic fish detection and measuring techniques has increased (Jing et al, 2017;Tušer et al, 2014;Zhang et al, 2014), but manual or semi-automatic counting and measuring is still the most common analysis method when using imaging sonar technology for monitoring fish populations (Atkinson et al, 2016;Lilja, Orell, et al, 2010;Lilja, Romakkaniemi, et al, 2010). However, in manual measurements, the consistency of human-generated lengths remains an issue that contributes to a measurement bias and interobserver error has been reported in many instances (Daroux et al, 2019;Hakkola, 2011;Keefer et al, 2017). Daroux et al (2019) also highlight a high intra-individual error and suggest that three to five measurements per fish on the best-quality frames will improve the length measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the need to specifically describe the difference between L T and L AV for each target species. Furthermore, Daroux et al (2019) detected an operator effect on the difference between L T and L AV .…”
mentioning
confidence: 95%
“…This data can be useful to differentiate species (Becker and Suthers, 2014;Grote et al, 2014), adults from juveniles of the same species (Doehring et al, 2011) or in the case of European eels, males from females (Vollestad, 1992). Several studies estimated the reliability of length estimates based on acoustic videos by comparing the known size (usually total length L T ) of different species to the length estimate from acoustic video (L AV ) in the laboratory (Hightower et al, 2013;Zhang et al, 2014;Cook et al, 2019;Daroux et al, 2019) or in the field (Burwen et al, 2010). These studies concluded that L AV could be either over estimated or under estimated compared to L T depending on the species (Hightower et al, 2013), its size (Daroux et al, 2019), the orientation of the fish compared to the camera and the detection range (Cook et al, 2019).…”
mentioning
confidence: 99%